The Poppy Lady : Moina Belle Michael and her tribute to veterans - Walsh, Barbara Elizabeth; Johnson, Layne (Honesdale, Pa. : Calkins Creek, 2012)
Looks at the life and career of Moina Bell Michael, who made the red poppy of Flanders Fields, a symbol to remind people of the sacrifice and courage of America's soldiers.
Includes bibliographical references.
6.0
3-6
850L
Keywords: Michael, Moina Belle, -- 1869-1944 -- Juvenile literature; Educators -- United States -- Biography -- Juvenile literature; Women -- United States -- Biography -- Juvenile literature; Michael, Moina Belle, -- 1869-1944.; Educators -- Biography; Women -- Biography; Nonfiction picture books; Biographies